1994
DOI: 10.1111/j.1439-0329.1994.tb00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Stem cankers on Swedish biomass willows caused by Cryptodiaporthe salicella and other fungi

Abstract: Field surveys and inoculation experiments were carried out in order to determine the most important stem‐canker fungi on willows planted for energy production. The pathogenicity of different fungal isolates and factors influencing infection were studied in the field and in greenhouse experiments, where canker extension was measured after inoculation either on dormant plants or on plants undergoing active growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Blue-strain fungus Ophiostoma spp. enters wood through frost cracks [67,[70][71][72]; Phoma herbarum has been reported to cause stem cankers via bark wounds and injuries as entry points [66,68,73]. Lastly, frost cracks could have contributed to the establishment of the infection of Chondrostereum purpureum, the most abundant white rot-causing basidiomycete in our data set, as bark lesions and other mechanical damage contribute to infection with this fungus [74,75].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Blue-strain fungus Ophiostoma spp. enters wood through frost cracks [67,[70][71][72]; Phoma herbarum has been reported to cause stem cankers via bark wounds and injuries as entry points [66,68,73]. Lastly, frost cracks could have contributed to the establishment of the infection of Chondrostereum purpureum, the most abundant white rot-causing basidiomycete in our data set, as bark lesions and other mechanical damage contribute to infection with this fungus [74,75].…”
Section: Discussionmentioning
confidence: 80%
“…Although none of the detected fungal genera directly corresponded to frost crack incidence or presence (Table 4), the ecology of several of the detected taxa is closely related to frost crack or other bark injuries [66][67][68]. Regarding Fusarium spp., one of the dominant plant pathogens in our data set, several studies have found associations between Fusarium canker development in aspens and bark wounds, such as pruning wounds, frost cracks, insect damage, and even beaver feeding ( [69] and references therein).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation